The Use of Educational Comics to Enhance Learning Interest in Pancasila Education at the Primary School Level - Erina Safira Ramadhani; Sukartono Sukartono (Journal of Innovation and Research in Primary Education, 2026)
Pancasila Education in Indonesian elementary schools faces pedagogical challenges characterized by teacher-centered instruction and low student learning interest, particularly in teaching abstract concepts such as rights and obligations. This quantitative study employed an ex post facto design to examine the relationship between educational comic media and fourth-grade students' learning interest in Pancasila Education. Data were collected from 68 students at SD Negeri 16 Purwodadi using validated questionnaires measuring educational comics characteristics and learning interest dimensions. Simple linear regression analysis was conducted to test the hypothesis at α = 0.05 significance level. Statistical analysis revealed that educational comic media significantly influenced student learning interest (β = 0.359, t = 3.129, p = 0.003), explaining 12.9% of variance in learning interest. The regression model demonstrated statistical significance (F = 9.789, p = 0.003), confirming that comics positively predict student engagement.  The findings support cognitive developmental theory and multimedia learning principles, demonstrating that visual narratives effectively transform abstract citizenship concepts into concrete, accessible learning experiences. Educational comics facilitate meaningful learning through multimodal presentation combining visual, textual, and narrative elements that align with elementary students' cognitive characteristics. These results suggest that comics serve as valuable complementary pedagogical tools when strategically integrated within student-centered instructional frameworks, contributing to enhanced engagement in value-based education.